The End of a Nation: Warithuddin Muhammad and Muslim Identity in the Nation of Islam - Derek R. Galyon (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
Warithuddin Muhammad’s tenure as the leader of the Nation of Islam (NOI) saw the attempted implementation of universalist doctrine that differed significantly from the particularism practiced by the movement’s founding prophet, Elijah Muhammad. Despite an apparent desire to distance the movement from Elijah Muhammad’s teachings of the intrinsic link between Blackness and Islam, race remained important for both Warithuddin and his followers. By partially embracing universalist interpretations that purported to view each race as inherently equal from an Islamic viewpoint, Warithuddin could easily be characterized as having tried to “deracialize” the Nation of Islam. With this shift, one would expect the importance of Blackness to significantly decrease within Warithuddin’s followers in favor of strengthened identification with the global umma (Muslim community). Yet, Warithuddin and his followers refrained from abandoning the significance of Blackness within Islam. Instead, they began to rely on classical Islamic historical narratives—rather than the appropriation of traits linked with socioeconomic privilege as Elijah Muhammad had done—in order to maintain a distinct Black American Muslim identity. In this article, I explore three unique aspects of Warithuddin Muhammad’s leadership within the American Muslim community in order to suggest both that race remained important for his movement and that his doctrinal shifts ultimately served to alter Black American Muslim identity by viewing the East—and specifically Arabia—as a powerful source of Islamic authority. After discussing his appropriation of Bilal ibn Rabah, a former Ethiopian slave who became a close companion to the Prophet Muhammad, I address the impact of heightened immigration from predominantly Muslim nation-states during the 1970s and its significance for Warithuddin Muhammad’s Qu’ranic exegesis before closing with an examination of his decision to deemphasize the narrative of countercitizenship that was dominant in his father's movement by recognizing the legitimacy of the United States government.
Keywords: Islam; Warithuddin Muhammad; Wallace Muhammad; Warith Deen Mohammed